From science to God : the mystery of consciousness and the meaning of light - Russell, Peter (Novato, California : New World Library, 2003)
This book offers a crash course in the nature of reality. It is the story of Peter Russell's lifelong exploration into the nature of consciousness - how he went from being a strict atheist, studying mathematics and physics at Cambridge University, to realising a profound personal synthesis of the mystical and scientific.
The great awakening.
Keywords: Spiritual life; Consciousness -- Religious aspects; Religion and science